The design of a hybrid spread-spectrum CSMA-CD protocol and its performance in high-speed integrated-services local-area networks - Pham Manh Lam; O'Farrell, T.; Lochmann, S.; Murch, A.; Takahashi, K.; Finnish International Development Agency (FINIDA),Finland (Bangkok : Asian Institute of Technology, 1992)
The research presented in this thesis consists of the design and investigation into the performance of a novel hybrid CDMA/CSMA-CD protocol for applications in High Speed Integrated Services Local Area Networks (HSIS LANs). A class of DSSS protocols which have a true capacity improvement per unit bandwidth over conventional contention protocols, such as Ethernet, have been identified. CSSS/CD is used as a generic name describing this class of protocols with various forms of channel sensing and collision detection. The protocol procedures of Connection, Data Transfer and Disconnection (including full-duplex capabilities) for High Speed Integrated Services Local Area Networks (HSIS LANs) are specified. Computer simulation models which can be used to analyse and examine the behaviour of the CSSS/CD protocols under varying design and operating conditions are devised. These models are built up using OPNET/M version 2.3 which is a workstation-based network simulation tool conceived by MIL 3 Incorporation. Finally, the delay/throughput performance of the new lP-CSSS/CD protocols are evaluated and compared with 1 P-CSMA/CD (Ethernet) for identical channel conditions. The advantage of these protocols is that they may be realised by only a physical layer change to the standard Ethernet protocol while achieving a true capacity improvement over Ethernet for large offered loads and large data rates, thus making these protocols ideally suited to HSLN applications
A thesis submitted in partial fulfillment of the requirement for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology,1992
Keywords: Spread spectrum communications